2008
DOI: 10.1371/journal.ppat.1000042
|View full text |Cite
|
Sign up to set email alerts
|

An Unbiased Systems Genetics Approach to Mapping Genetic Loci Modulating Susceptibility to Severe Streptococcal Sepsis

Abstract: Striking individual differences in severity of group A streptococcal (GAS) sepsis have been noted, even among patients infected with the same bacterial strain. We had provided evidence that HLA class II allelic variation contributes significantly to differences in systemic disease severity by modulating host responses to streptococcal superantigens. Inasmuch as the bacteria produce additional virulence factors that participate in the pathogenesis of this complex disease, we sought to identify additional gene n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 61 publications
1
57
1
Order By: Relevance
“…A set of studies by Miyairi and associates revealed that susceptibility to Chlamydia psittaci is a simple trait that is controlled by a single host locus that encodes p47 GTPases [74,100]. Another study revealed that differential susceptibility to group A Steptococci is also controlled by a single host genetic locus [122]. In contrast, a study by Yadav and colleagues [121] and the present study revealed that susceptibility to the bacterial pathogens Yersina pestis and Bp, respectively, involve multiple host loci.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…A set of studies by Miyairi and associates revealed that susceptibility to Chlamydia psittaci is a simple trait that is controlled by a single host locus that encodes p47 GTPases [74,100]. Another study revealed that differential susceptibility to group A Steptococci is also controlled by a single host genetic locus [122]. In contrast, a study by Yadav and colleagues [121] and the present study revealed that susceptibility to the bacterial pathogens Yersina pestis and Bp, respectively, involve multiple host loci.…”
Section: Discussioncontrasting
confidence: 57%
“…These findings are not surprising in light of findings that genetic factors play a key role in susceptibility to a wide range of other infectious diseases. Published findings have identified host genetic factors that are critical for variable susceptibility to intracellular parasites [115], viruses [116][117][118][119][120], and both intracellular [74,100,121] and extracellular [122] bacterial pathogens. Moreover, recent genome-wide studies have established novel associations between common polymorphisms and susceptibility to several infectious diseases that are responsible for significant morbidity and/or mortality in humans [73,100,123,124].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the bacteria produce a number of additional, important virulence factors that must also participate in the pathogenesis of GAS sepsis. The overall aim of my study was to identify additional host factors modulating susceptibility to severe GAS sepsis and to identify host genes and pathways involved in this disease (Aziz et al, 2007;Abdeltawab et al, 2008).…”
Section: Streptococcal Sepsis As a Model Of Host-pathogen Interactionsmentioning
confidence: 99%
“…RI and ARI strains have been successfully used to map quantitative trait loci (QTLs) associated with various phenotypes and diseases (Hardy et al, 2001;Grizzle et al, 2002;Chesler et al, 2005;Miyairi et al, 2007;Abdeltawab et al, 2008). RI and ARI strains of mice are the progeny of two ancestral inbred strains.…”
Section: Systems Genetics Approach -Definition and Toolsmentioning
confidence: 99%
See 1 more Smart Citation